Statistical Analysis for waste generation Prediction based on the Population Growth in Tangerang: An environmental Perspective - Utami, Ika Wahyu; Najih, Muhammad; Putri, Larasati Rizky; Su'udi, Bambang Cholis (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
Tangerang is counted among Indonesia's fastest-growing industries and population since it is located near the capital. At the current rate of population growth, the population by 2035 is expected to reach more than 2 million by appliying the geometric method. Rapid population growth has severe environmental damage. A simple linear regression calculation was applied to predict the Tangerang waste generation and it is expected to grow to 1,57 million tonnes by 2035. The Pearson's correlation was used to examine the impact of population growth in Tangerang on waste generation. Overall, there is a positive correlation between population growth and waste generation. The increase in the amount of waste can affect the formation of leachate. Rawa Kucing is the main Tangerang landfill that implements an open dumping system in its waste management. One of the negative impacts of the open dumping system is the potential for leachate generation. This study performed a simple calculation of leachate volume to illustrate leachate generation in Rawa Kucing. The more leachate produced, the greater the level of contamination since it contains highly toxic components, and it will escape from the Rawa Kucing landfill, contaminating the groundwater, potentially polluting the environment and harming human health.